2013
DOI: 10.7150/ijms.5457
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation and Pre-activation of TRAF3 and TRAF5 in Inflammatory Bowel Disease

Abstract: Objective: TRAF3 and TRAF5 share a common ancestral gene, and interact as essential components of signaling pathways in immunity. TRAF3 and TRAF5 are overexpressed in the colon of rat/mouse models with colitis. However, the expressions of TRAF3 and TRAF5 in patients with inflammatory bowel disease have not been elucidated. The aim of the present study is to explore the potential roles of TRAF3 and TRAF5 in patients with inflammatory bowel disease.Methods: Plasma levels of TRAF3 and TRAF5 proteins were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Furthermore, in human inflammatory bowel disease (IBD) specimens, the mRNA level of EZH2 was negatively correlated with that of TRAF2 or TRAF5, suggesting that the decreased EZH2 expression in IBD patients causes augmented TNF-a-induced NF-kB signaling mediated by TRAF2 and TRAF5. In support of this, the expression of TRAF2 and TRAF5 was upregulated in the inflamed colonic tissues of IBD patients (38,39). In addition, the overexpression of TRAF2 or TRAF5 might be involved in colon cancer development (40,41).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, in human inflammatory bowel disease (IBD) specimens, the mRNA level of EZH2 was negatively correlated with that of TRAF2 or TRAF5, suggesting that the decreased EZH2 expression in IBD patients causes augmented TNF-a-induced NF-kB signaling mediated by TRAF2 and TRAF5. In support of this, the expression of TRAF2 and TRAF5 was upregulated in the inflamed colonic tissues of IBD patients (38,39). In addition, the overexpression of TRAF2 or TRAF5 might be involved in colon cancer development (40,41).…”
Section: Discussionmentioning
confidence: 75%
“…It has previously been reported that soluble TRAF5 levels are increased in plasma and peripheral blood mononuclear cells from patients with Crohn's disease and ulcerative colitis (21). other studies have implicated TRAF5 in carcinogenesis attributable to increased levels in splenic marginal zone lymphoma (22) and Hodgkin-Reed-Sternberg cells (23).…”
Section: Discussionmentioning
confidence: 98%
“…It has been well established that TRAF5 is involved in the pathogenesis of several inflammatory and autoimmune diseases. The expression levels of TRAF5 increase in patients suffering from inflammatory bowel disease, and there is a weak correlation between TRAF5 and endoscopic disease activity index in patients with ulcerative colitis (16). Also, TRAF5 has been identified as a strong candidate for the rheumatoid arthritis susceptibility gene in the British population (17), and it is involved in the development of acute anterior uveitis (18), according to genetic polymorphism analysis in Han Chinese.…”
Section: Discussionmentioning
confidence: 99%